The Effectiveness Of Photodynamic Therapy In Combination With Infrared Laser Exposure - Umarkhodjaev A.M.; Gulyamov S.S.; Umarkhodjaeva G.M. (International Journal of Medical Sciences And Clinical Research, 2025)
Keloid is a human-specific illness that is poorly understood. Similar to keloids, hypertrophic scars have the potential to eventually develop into keloids. Long treatment/follow-up periods and uneven efficacy are the main drawbacks of the conventional treatments for these scars. Thus, a novel therapy that works for every instance of aberrant scarring is required. PDT could be one choice. In reconstructive and aesthetic dermatology, post-burn scars continue to be one of the most challenging issues. Particularly when they are restricted to visible body parts, they frequently result in physical discomfort, psychological anxiety and difficulties adjusting to social situations. The unique features of scar tissue production, healing dynamics, and skin type may make standard treatment procedures ineffective. A viable alternative is a customized strategy utilizing combined laser and PDT. Through the combined effects of laser ablation and cellular-level photochemical reactions brought on by photosensitizers, this dual-modality approach improves therapeutic efficacy. This strategy seeks to reduce adverse effects and maximize therapeutic results. Although further clinical research, especially randomized clinical trials, is required, PDT seems to have a promising function in keloid and hypertrophic scar therapy. A safe and efficient way to treat burn scars is using customized laser-photodynamic treatment. The customized method makes it possible to create treatment plans that are most suited to the patient's scar characteristics, which improves clinical results and raises patient satisfaction. This method ought to be regarded as a useful supplement to current methods for managing scars.